Laparoscopic Cholecystectomy for a giant Gallstone - Khan, Irfan Jan; Alahmad, Murad; Aurif, Fahad; Mir, Najeeb Hussain (Archives of Clinical and Medical Case Reports, 2022)
Introduction: Cholelithiasis is very common, but giant gallstones - gallstones bigger than 5 cm in diameter, are very rare. It is very challenging to remove them laparoscopically, especially in emergency situations. Case Report: A 69-year-old female complained of right upper abdominal pain with vomiting for 1 day. Abdominal ultrasound indicated acute cholecystitis and a single, extremely large gallstone (9cm). Emergency laparoscopic cholecystectomy was performed successfully. Discussion: Gallstone over 5 cm in diameter is very rare. Laparoscopic Cholecystectomy (LC) is very difficult for these cases, especially in the emergency situations. Laparoscopic cholecystectomy can, however, be safely performed in experienced hands. To the best of our knowledge, this is one of the biggest gallstones managed laparoscopically. Conclusion: Although the presence of giant gallstones poses technical challenges, laparoscopic cholecystectomy can be safely performed in the experienced hands. However, if the anatomy cannot be delineated clearly, open surgery remains the safe option.